Understanding the Importance of the Length of Global Product Rollout: An Examination in the Motion Picture Industry. Issue 4 (December 2017) - Griffith, David A.; Yalcinkaya, Goksel; Rubera, Gaia; Giannetti, Verdiana
Employing the resource-based view of the firm and the competitive forces perspective, the authors examine how brand equity (star power, director power, and brand extensions), financial resources, and competitive intensity serve both as antecedents to the length of global product rollout and as moderators of the effect of length of global product rollout on global product performance. The results, based on data from the motion picture industry, demonstrate that brand equity, financial resources, and competitive intensity result in shorter global product rollout and that shorter global product rollout enhances global product performance. They also find that brand equity and financial resources operate as moderators, magnifying the effect of length of global product rollout on global product performance. Implications for international marketing academics and practitioners are presented.